Implementasi Kincir Aerator Berbasis Tenaga Surya Pada Tambak Udang di Kabupaten Pangkep - Muhammad Syahid; Azwar Hayat; Fahrul; Lukman Kasim; Rudi Amme (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Pangkajene Islands Regency is one of the centers producing fishery products such as shrimp and milkfish. Shrimp is one of Indonesia's main export commodities in the fisheries sector. However, the productivity of ponds in Pangkep Regency is still relatively low because they are still managed traditionally without aerators. The use of an aerator will increase the oxygen content in the pond so that productivity can be increased. Limited access to electricity for farmers who are far from settlements is one of the problems with the use of aerators which are still not widely used. Therefore, with the help of solar panels to supply electricity to the aerator wheels, farming can run more economically, efficiently and can increase productivity. The solar aerator system is assembled and tested for performance both in the laboratory and during implementation. Then socialization and demonstrations on the use of solar-based aerators were carried out.